Remittances, Home Towns Association And Sustainable Development At The Communal Level: A Case Of Ikorodu North Local Council Development Of Lagos State, Nigeria - Olowa, Olatomide Waheed (European Journal of Sustainable Development, 2016)
Hometown Associations (HTAs) are migrant organizations in host communities, with members from the same community of origin, which send collective remittances back to their hometown for community development Purposes. This study examined HTA formation and institutional partnership arrangements with Community Development Associations (CDAs) in Ikorodu North Local Council Development Area (LCDA) of Lagos State. Data were collected using semi-structured interviews conducted on 100 participants comprising migrants families, CDAs’ and government officials purposively selected for the study. The findings from the study suggest there is a role for CDAs to help leverage remittances to support community development in migrant source communities in the LCDA. The results highlight the importance of HTA and CDA partnership and the need to involve beneficiaries in development projects to make sure partnership arrangements are effective. Specifically, the empirical evidence showed that institutional partnerships have potential to help HTAs evolve to become a lasting development institution. Key Words: Collective remittances, Home Town Association, Community Development Association, Local Council Development Area, Lagos State, Nigeria.